Perbandingan Model Pembelajaran Reciprocal Teaching dengan Bamboo Dancing Berbasis Cooperatif Learning - Roikhatul Machbubah; Khoirun Nisa' (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2019)
This study aims to determine the comparison between Reciprocal Teaching learning models and Bamboo Dancing to find out which learning models are effectively used. The difference between Reciprocal Teaching and Bamboo Dancing learning models lies in the way the teaching and learning process is delivered. Reciprocal Teaching Model prioritizes language style or speaking style of students in delivering the material presented, while the Bamboo Dancing learning model prioritizes the activeness of a student in channeling what he gets then they exchange ideas with other friends.